Exercise metabolism - Spriet, Lawrence L.; Hargreaves, Mark 1961- (Human Kinetics, 2006)
Exercise Metabolism, Second Edition, provides a systematic, in-depth examination of the regulation of metabolic processes during exercise. Exercise physiologists, exercise biochemists, and biochemists will find this book a comprehensive reference, using the up-to-date information and the nearly 1,000 references in their own research and writing. In addition, graduate students in these disciplines can learn firsthand about the various regulations of metabolic processes during exercise as they prepare for careers in exercise physiology or biochemistry. Written by internationally recognized researchers, Exercise Metabolism, Second Edition, is both revised and expanded while retaining the essential elements of the first edition. It delves into the mobilization and utilization of substrates--glucose, lipid, and protein--during physical activity, and it explores metabolic factors in fatigue and metabolic adaptations to endurance training. Chapter 1 provides an overview of exercise metabolism. Metabolism during high-intensity exercise and the transition from rest to exercise are covered in chapter 2, which details the so-called anaerobic energy pathways. Chapter 3 discusses the effects of exercise on carbohydrate metabolism in skeletal muscle, while chapter 4 provides an overview of the important metabolic functions of the liver during exercise. Chapter 5 is a new chapter that addresses lactate transport in skeletal muscle, given the increased understanding of this topic since the first edition was published. Chapters 6 and 7 summarize the effects of exercise on lipolysis in adipose tissue and lipid metabolism in skeletal muscle, respectively. The contribution of protein and amino acids to exercise metabolism is discussed in chapter 8. Finally, metabolic factors in fatigue and the metabolic adaptations to endurance training are reviewed in chapters 9 and 10, respectively. Chapter-ending summaries help to condense the information and facilitate understanding. Exercise Metabolism, Second Edition, is a valuable reference to exercise physiologists, exercise biochemists, and biochemists, and it serves as an ideal text for graduate students in these disciplines.